The effectiveness of the academic self and its relationship to the trend towards e-learning among Palestinian university students in light of the Corona pandemic - Al- Shorbagi, Eyad Samer (Journal of Educational and Psychological Sciences, 2020)
The study aimed to identify the level of effectiveness of the academic self and the level of trend towards e-learning among university students in light of the Corona pandemic in light of some variables. Academic Self Effectiveness Prepared by Kulab (2019), And the measure of the trend towards e- learning was prepared by Al- Sharif (2016), and the study found that the effectiveness of the academic self among the members of the study sample was average in general, with an arithmetic average (3.09) and a percentage (62%), and that the students ’attitudes towards e- learning were high and with an arithmetic average (3.50) and as a percentage (70%) The results also revealed the existence of a positive statistically significant correlational relationship between the academic self- effectiveness of Palestinian university students and their attitudes towards e- learning, and the results also showed that there are no differences in the effectiveness of the academic self among Palestinian university students and their attitudes towards using e- learning due to the variable of gender and university The study recommended that universities should pay attention to introducing e- learning in university education, and to spread electronic culture among students, the bodies responsible for preparing curricula by strengthening the set of beliefs related to academic self- efficacy, which in turn contribute to maintaining a level of positive motivation towards study in general.